1974
DOI: 10.1002/1097-0142(197404)33:4<970::aid-cncr2820330412>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Pseudosarcoma of the skin.An electron microscopic study and comparison with the fine structure of the spindle-cell variant of squamous carcinoma

Abstract: An ultrastructural study of a postirradiation pseudosarcoma of the skin is reported and compared to the spindle cell variant of squamous carcinoma in order to exclude epithelial histogenesis of the former. The pseudosarcoma tissue was composed of cells having the ultrastructural features characteristic of myofibroblasts. The cells of the spindle cell variant of the squamous carcinoma demonstrated the presence of tonofibrils which were joined by many desmosomes. These findings contradict the concept of an epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…Weedon and Kerr 20 reviewed two AFXs using electron microscopy and found that the tumor cells resembled myofibroblasts. Woyke and colleagues 21 concluded the same thing based on their electron microscopy findings. Another group 2 found a tumor with characteristics of fibroblasts, but in another AFX they examined, they concluded that cells most resembled Langerhans‐like cells.…”
Section: Pathogenesis/etiologymentioning
confidence: 83%
“…Weedon and Kerr 20 reviewed two AFXs using electron microscopy and found that the tumor cells resembled myofibroblasts. Woyke and colleagues 21 concluded the same thing based on their electron microscopy findings. Another group 2 found a tumor with characteristics of fibroblasts, but in another AFX they examined, they concluded that cells most resembled Langerhans‐like cells.…”
Section: Pathogenesis/etiologymentioning
confidence: 83%
“…8,[14][15][16][17][18][19] Although Langerhans-like cells have also been observed by electron microscopy, 20 these cells probably correspond to accompanying nontumoral cells. 21 AFX shares some clinical features with cSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural features can also be used to determine if an anaplastic tumor is of epithelial origin based on the presence of intercellular bridges, desrnosome-tonofilament complexes, and keratohyaline granules (3,24,38). Desmosomes in poorly differentiated or anaplastic carcinomas can be small and difficult to identify.…”
Section: Rt-pcr Analysis Of Tumor Tissue For Expression Of the Ras Trmentioning
confidence: 99%
“…In this regard, spindle cell tumors have been reported in various organs in humans and experimental animals (7,18,19,26,38,39). These lesions are malignant, aggressive, and of unclear histiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation